Doctor of pharmacy as a career option: a cross-sectional study exploring PharmD students and practitioners expectations in Jordan - Suha A. AlMuhaissen; Eman Elayeh; Rawia Sharaydih; Taibah M. Abdullah; Aseel AlShalalfeh; Hatim S. AlKhatib (BMC, 2023)
Abstract Objective This study aimed to (1) investigate the expectations and preferences of PharmD students and practitioners regarding their role in the health care system, and (2) to contrast those expectations and preferences of PharmD practitioners with real-life practice in Jordan. Methods Two cross-sectional descriptive questionnaires were used to collect data from PharmD students and PharmD practitioners in Jordan. A total number of 330 students and 280 practitioners were interviewed. The responses to all questions were encoded, entered, and summarized as frequencies and percentages or as means and standard deviations. Comparisons between groups were performed using Chi-square test. A p-value of < 0.05 was considered significant. Results Both PharmD students and practitioners chose working as a clinical pharmacist in a hospital as their first-choice job. However, their second and third jobs choices were significantly different as practitioners opted for income as a main criterion for job selection. Interestingly, salary expectations by PharmD students were significantly higher than the reality as reported by PharmD practitioners. Both students and practitioners placed the work environment as the highest priority criterion for making a work choice on the work environment. In general, both students and practitioners agree on the ideal roles of PharmD graduate with the issues of prescribing and compounding responsibilities being the ones with the highest disparity between practitioners and students. Significant differences were found between the student's and practitioner's perceptions of the ideal role of a PharmD in and the current professional practice in Jordan. Conclusion Job preferences and salary expectations differ significantly between students and practitioners. Professional orientation of PharmD. students should be implemented to minimize misconceptions of their job nature, availability, and compensations. The fact that students do not prefer to work in a community pharmacy should be addressed by educational institutions and professional organizations. The prescribing and compounding responsibilities of pharmacists should be also emphasized in the curricula of pharmacy schools and worked in by professional organization to achieve optimal implementation in real-life practice.